Relationships Between C4 Enzyme Activities and Yield in Soybeans (Glycine max (L.) Merr.) - Shan-shan HUANG; Chang-suo LI; Ming-liang YANG; Wen-bin LI; Ji-an WANG (Journal of Integrative Agriculture, 2013)
To study the relationships between C4 enzyme activities and yield, C4 enzyme activities (phosphoenolpyruvate carboxylase (PEPCase), NADP-malate dehydrogenase (NADP-MDH), NADP-malic enzyme (NADP-ME), and pyruvate phosphate dikinase (PPDK)) in different organs of ten soybean cultivars with different yields were measured at different growth stages in China. The result showed that four enzyme activities in C4 pathway were obviously different among cultivars, especially PPDK activity was not detected in the leaves of Dongnong 1567 and Dongnong 1068 and the young leaves of Gongjiao 9107-1 and Dongnong 97–172, but there were weak activities in pod coats. The order of C4 enzyme activities is young leaves < old leaves < pod coats. The correlation coefficients between PEPCase activity and yield and between NADP-MDH activity at blooming stage and yield were 0.6979 and 0.6565, respectively, and both reached the significant level (5%), and PEPCase activity kept significant positive correlation with plant photosynthetic rate. There was a negative correlation between NADP-ME activity and yield, and no correlation was found between PPDK activity and yield.